Effect of kit ligand on natriuretic peptide precursor C and oocyte maturation in cattle - Lima, Paula F. [UNESP]; Ormond, Cinthia M. [UNESP]; Caixeta, Ester S. [UNESP]; Barros, Rodrigo G. [UNESP]; Price, Christopher A.; Buratini, Jose [UNESP] (Bioscientifica Ltd, 2016)
In vitro maturation (IVM) of oocytes in cattle is inefficient, and there is great interest in the development of approaches to improve maturation and fertilization rates. Intraovarian signalling molecules are being explored as potential additives to IVM media. One such factor is kit ligand (KITL), which stimulates the growth of oocytes. We determined if KITL enhances oocyte maturation in cattle. The two main isoforms of KITL (KITL1 and KITL2) were expressed in bovine cumulus-oocyte complexes (COC), and levels of mRNA increased during FSH-stimulated IVM. The addition of KITL to the culture medium increased the percentage of oocytes that reached meiosis II but did not affect cumulus expansion after 22 h of IVM. Addition of KITL reduced the levels of mRNA encoding natriuretic peptide precursor C (NPPC), a protein that holds oocytes in meiotic arrest, and increased the levels of mRNA encoding YBX2, an oocyte-specific factor involved in meiosis. Removal of the oocyte from the COC resulted in increased KITL mRNA levels and decreased NPPC mRNA levels in cumulus cells, and addition of denuded oocytes reversed these effects. Taken together, our results suggest that KITL enhances bovine oocyte nuclear maturation through a mechanism that involves NPPC, and that the oocyte regulates cumulus expression of KITL mRNA.